Automated fruit grading system - Ali, Mohammed A. H.; Wong, Kelvin Thai (IEEE, 2017)
In recent years, automatic visual inspection technology has become more potential and important to fruit grading applications. This is due to that the quality of fruits are the important factor for the consumer and so essential for marketing a uniform high quality products. The automated fruits grading technique have been set up to reduce the production costs and improve fruit quality and replace the manual technique for grading of fruits as manual inspection is facing problems in maintaining consistency and uniformity. Two kinds of fruits have been inspected in this project; namely are apple and mango. A prototype of an automated fruit grading system is designed and developed in this paper to detect the defects on of the surface of fruits. The system is capturing the fruit’s image using camera and the fruits are placed onto of a rotating desk. The image is transmitted then to the processing level where the grading is done using MATLAB.